Dua Wajah Paralegal pada Komunitas LBH APIK dalam Proses Pendampingan Korban Kekerasan Seksual di Wilayah Jabodetabek - Keysya Ainina; Atika Sri Devi; Sefia Citra Adittya; Riana Riana; Fitri Agustin; Didi Pramono (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Sexual violence is a widespread issue in Indonesia, particularly in the Jabodetabek area, and there is a need for assistance in handling these cases. Various forms of sexual violence, most of which target women, require the help of organizations like LBH APIK to provide legal assistance and defend the women’s right, especially victims of sexual violence. The figure behind the community of LBH APIK is Paralegal, which plays a significant role in managing cases, especially those related to sexual violence. This article is written with the intention of delving deeper into the role of LBH APIK, specifically paralegals, in handling sexual violence cases in the Jabodetabek area. The source of this article is the YouTube channel Watch Doc Documentary, with a data collection method based on national and international journal studies. The final result of this writing is that Paralegal has two faces in their work, which can be analyzed by using Erving Goffman’s dramaturgy theory.